Comparison of the Effect of Different Local Analgesia Administration Techniques in Total Hip Arthroplasty: A Retrospective Comparative Cohort Study. (26th July 2021) - Hashimoto, Akira; Sonohata, Motoki; Kawaguchi, Atsushi; Kii, Sakumo; Hirata, Hirohito; Mawatari, Masaaki
Abstract : Objective . To improve postoperative pain management, several authors have described the use of periarticular injection (PAI) or intra-articular injection (IAI) following total hip arthroplasty (THA). However, no comparative studies examining the results between PAI and IAI following THA have been published. This study aimed to evaluate the analgesic and anti-inflammatory effects of PAI and IAI following THA. Methods . This single-center, retrospective cohort study enrolled patients who underwent unilateral primary THA. A total of 278 patients (281 hips) were included in the final analyses, with 112 patients (113 hips) in the control group, 85 patients (87 hips) in the PAI group, and 81 patients (81 hips) in the IAI group. Numeric rating scale (NRS) scores and laboratory data were assessed preoperatively and on postoperative days (POD) 1 and 7. Results . NRS scores, creatine phosphokinase, and C-reactive protein levels in the PAI and IAI groups were significantly lower than those in the control group on POD 1 and 7. D-dimer levels were significantly lower in the PAI and IAI groups than in the control group on POD 7. The white blood cell count was significantly higher in the PAI and IAI groups than in the control group on POD 1 and 7. Aspartate transaminase, alanine aminotransferase, blood urea nitrogen, and creatinine levels were within the reference ranges in all three groups at all time points. NRS scores and laboratory data showed no significant differences between the PAI and IAI groups at all time points. Conclusion . PAI and IAI have equivalent analgesic and anti-inflammatory effects. Considering the technical challenges of PAI, IAI may be preferable because of its simplicity in the case of using a closed suction drain.